Antineoplastic Agents 579. Synthesis and Cancer Cell Growth Evaluation of E-Stilstatin 3: A Resveratrol Structural Modification - Pettit, George R. (2009)
As an extension of our earlier structure/activity investigation of resveratrol (1a) cancer cell growth inhibitory activity compared to the structurally related stilbene combretastatin series (e.g., 2a), an efficient synthesis of E-stilstatin 3 (3a) and its phosphate prodrug 3b was completed. The trans-stilbene 3a was obtained using a convergent synthesis employing a Wittig reaction with phosphonium bromide 9 as the key reaction step. Deprotection of the Z-silyl ether 13 gave E-stilstatin 3 (3a) as the exclusive product. The structure and stereochemistry of 3a was confirmed by X-ray crystal structure determination.